(3EQTGO GdeSJQTOjfs - (3GdHGHQJj , eMeO Hf eMeO Hf eMehO Hf TeS GdOjf Hf LeGd GdOjf GdQhej, Gced GdOjf CHh YHO Gddg,J (B786 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG eNJUQ ai Gdabg Cdag GdTjN Cced GdOjf eMeO GdMfai jTJed Ydi ebOeI hcJGHjf hNGJeI Ydi ePgH GdEeGe GdCYXe CHj MfjaI QMeg Gddg QMeI hGSYI s
(3BNQgG (B:s
(3Je cJGH EQTGO GdeSJQTOjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B42 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B298s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3abg Mfai (B953) s
Keywords: (3Gdabg GdMfajs